Efektivitas Media Pembelajaran Interaktif (Quiziz) terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII-C MTs Nu Nurul Ulum - Zahra, Naila Az; Amalia, Avina Imma; Qulub, Faizuna Tathmainnul; Aziza, Muhammad; Nur, Dany Miftah M. (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
The phenomenon in the modern era is characterized by the rapid development of technology, information and communication. Learning media is used as an intermediary to convey messages or information to students. Using creative media can influence students to like the subject. In this journal, researchers used an experimental research method with a descriptive quantitative approach. With a research sample of VIII C MTs NU Nurul Ulum students totaling 29 students. The results in this study are decreased, it shows that the interactive learning method using the Quiz application is less effective in learning in class VIII-C MTS Nu Nurul Ulum. This is evidenced by the minimum pretest score of 60 and the maximum score of 86 and for the minimum post test score of 20 and the maximum score of 85. The average pretest is 74.38 and for the post test is 72.59. The results of the pretest and post test have decreased